What is #f(x) = int xe^(x^2-1)+2x dx# if #f(0) = -4 #?

Answer 1

#f(x)=1/2e^(x^2-1)+x^2-4-1/(2e)#

Split up the integral:

#f(x)=intxe^(x^2-1)dx+int2xdx#
For the first integral, use substitution: let #u=x^2-1#, which implies that #du=2xdx#.
Multiply the integrand by #2# and the exterior of the integral by #1/2#.
#f(x)=1/2int2xe^(x^2-1)dx+int2xdx#
Substituting in #u=x^2-1# and #du=2xdx#:
#f(x)=1/2inte^udu+2intxdx#
Note that #inte^udu=e^u+C#. We will refrain from adding the constant of integration until we evaluate the second integral.
#f(x)=1/2e^u+2intxdx#
Since #u=x^2-1#:
#f(x)=1/2e^(x^2-1)+2intxdx#
In order to integrate #2intxdx#, use the rule #intx^ndx=x^(n+1)/(n+1)+C#, where #n!=-1#.

Applying this rule:

#f(x)=1/2e^(x^2-1)+2((x^(1+1))/(1+1))+C#
#f(x)=1/2e^(x^2-1)+x^2+C#
Now, we can determine the value of #C# using the initial condition #f(0)=-4#.
#-4=1/2e^(0^2-1)+0^2+C#
#-4=1/2e^-1+C#
#-4-1/(2e)=C#

Hence:

#f(x)=1/2e^(x^2-1)+x^2-4-1/(2e)#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To find ( f(x) ), integrate the given function with respect to ( x ), then use the provided initial condition ( f(0) = -4 ) to find the constant of integration.

( f(x) = \int (xe^{x^2 - 1} + 2x) , dx )

Integrating ( xe^{x^2 - 1} ) with respect to ( x ) gives:

( \int xe^{x^2 - 1} , dx = \frac{1}{2} e^{x^2 - 1} + C )

And integrating ( 2x ) with respect to ( x ) gives:

( \int 2x , dx = x^2 + C_2 )

Now, ( f(x) ) becomes:

( f(x) = \frac{1}{2} e^{x^2 - 1} + x^2 + C )

Given ( f(0) = -4 ), we can substitute ( x = 0 ) into the equation:

( -4 = \frac{1}{2} e^{0^2 - 1} + 0^2 + C )

( -4 = \frac{1}{2} e^{-1} + C )

( -4 + 2e^{-1} = C )

( C = 2e^{-1} - 4 )

Therefore, the function ( f(x) ) is:

( f(x) = \frac{1}{2} e^{x^2 - 1} + x^2 + 2e^{-1} - 4 )

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7